2014
DOI: 10.1097/yic.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine extended-release treatment of hoarding disorder

Abstract: Objectives Hoarding Disorder, classified as a separate disorder in DSM-5, is a common, chronic, and potentially disabling syndrome that can be difficult to treat. Only one prior study prospectively measured response to pharmacotherapy in compulsive hoarders, finding that hoarders responded as well to paroxetine as did non-hoarding OCD patients. However, paroxetine was not tolerated well in that study, and overall response was moderate. Therefore, we conducted an open-label trial of venlafaxine extended-release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 75 publications
0
38
1
2
Order By: Relevance
“…[47][48][49] Psicoterapia Pelo nosso conhecimento, existem quatro revisões sobre o tratamento psicoterápico das dificuldades relacionadas à acumulação. 47 55 Em uma série de casos, 4 pacientes com TA sem TDAH comórbido foram tratados com metilfenidato de liberação controlada por 4 semanas (dose média de 50 ± 9 mg/ dia). Dois participantes tiveram redução modesta dos sintomas de acumulação mensurados pelo SI-R (25 e 32%), especialmente em relação à aquisição excessiva.…”
Section: Tratamentounclassified
“…[47][48][49] Psicoterapia Pelo nosso conhecimento, existem quatro revisões sobre o tratamento psicoterápico das dificuldades relacionadas à acumulação. 47 55 Em uma série de casos, 4 pacientes com TA sem TDAH comórbido foram tratados com metilfenidato de liberação controlada por 4 semanas (dose média de 50 ± 9 mg/ dia). Dois participantes tiveram redução modesta dos sintomas de acumulação mensurados pelo SI-R (25 e 32%), especialmente em relação à aquisição excessiva.…”
Section: Tratamentounclassified
“…Selective serotonin reuptake inhibitors [13][14][15][16], Serotoninnorepinephrine reuptake inhibitors [17], Central nervous system stimulants [18] and atypical antipsychotic agents [19] have been administered for HD, but results from pharmaceutical treatment trials for hoarding are equivocal.…”
Section: Pharmaceutical Treatmentmentioning
confidence: 99%
“…29 A similar small openlabel study of 24 patients suggested extended-release venlafaxine may be effective for the treatment of hoarding disorder and was well tolerated. 30 Authors of a small case series which examined the effectiveness of methylphenidate in patients with significant hoarding. However, only 2 out of 4 patients in the series demonstrated benefit, and the results were modest.…”
Section: Pharmacotherapymentioning
confidence: 99%